Bacteriophage ZCKP1: A Potential Treatment for Klebsiella pneumoniae Isolated From Diabetic Foot Patients - Taha, Omar A.; Connerton, Phillippa L.; Connerton, Ian F.; El-Shibiny, Ayman (Frontiers in Microbiology, 2018)
The recorded growth in infection by multidrug resistant bacteria necessitates prompt efforts toward developing alternatives to antibiotics, such as bacteriophage therapy. Immuno-compromised patients with diabetes mellitus are particularly prone to foot infections by multidrug resistant Klebsiella pneumoniae, which may be compounded by chronic osteomyelitis. Bacteriophage ZCKP1, isolated from freshwater in Giza, Egypt, was tested in vitro to evaluate its lytic activity against a multidrug resistant K. pneumoniae KP/01, isolated from foot wound of a diabetic patient in Egypt. Characterization of ZCKP1 phage indicated that it belonged to the Myoviridae family of bacteriophages with a ds-DNA genome size of 150.9 kb. Bacteriophage ZCKP1 lysed a range of osteomyelitis pathogenic agents including Klebsiella spp., Proteus spp. and E. coli isolates. The bacteriophage reduced the bacterial counts of host bacteria by ≥2 log10 CFU/ml at 25°C, and demonstrated the ability to reduce bacterial counts and biofilm biomass (>50%) when applied at high multiplicity of infection (50 PFU/CFU). These characteristics make ZCKP1 phage of potential therapeutic value to treat K. pneumoniae and associated bacteria present in diabetic foot patients.